Nutrition, migration and family economics in developing countries : three essays - (:unkn) unknown (My University, 2025)
This dissertation is composed of three empirical essays in economics, positioned at the intersection of development economics, health economics, and migration and family economics, with a shared focus on nutrition in sub-Saharan Africa.Chapter 1 serves as a general introduction, presenting the current context of malnutrition in developing countries, the motivations behind this thesis, and the overarching concepts such as the household, mobility, and geographic dimensions. It also provides a summary of the results and contributions of each chapter.Chapter 2 analyzes the dynamics of the double burden of malnutrition (DBM) and overweight or obesity (OVOB) using South African longitudinal data. To investigate whether DBM (the coexistence, within the same household, of at least one overweight or obese person and one underweight person) is a transient or persistent phenomenon, a dynamic random-effects probit model is employed. The findings suggest that the double burden is a transitory phenomenon: most affected households do not retain this status in subsequent survey waves. In contrast, OVOB households (with at least one overweight or obese person but no underweight individuals) exhibit strong persistence of their status, also reflecting the long-term stability of overweight and obesity at the individual level. Conversely, the transient nature of DBM can be explained by the tendency of underweight individuals to transition out of this condition over time.Chapter 3 investigates the effect of migration on the nutritional outcomes of the left behind—individuals who previously co-resided with a migrant. Utilizing longitudinal data from Ghana and a combination of matching and difference-in-differences, the analysis reveals that internal migration negatively impacts the nutritional status of left-behind individuals, particularly children. The primary channel driving the adverse nutritional impact appears to be the short-term disruptive effect caused by migratio
Keywords: African Research